The Paradox of Secularism and The Construction of Structural Islamophobia in France: : A Study of Public Policy, Media Representation, and Muslim Identity - Ahmad Mukafi; Abd A'la; Amir Maliki Abitolkha (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This study aims to analyze the paradox of French secularism or laïcité, which promises universal equality but instead results in structural exclusion for Muslim communities. Using a qualitative approach with a literature review, this research applies Philippe Bourbeau's securitization theory framework to examine various legal documents, public policy texts, and media discourse from 1905 to 2023. The main findings show that the principle of laïcité has undergone a transformation of function from a foundation of state neutrality to an instrument of securitization that legitimizes institutionalized Islamophobia. Data analysis reveals that state and media actors systematically frame Muslim identities and their religious attributes as an existential threat to republican values, leading to social alienation. This study concludes that national cohesion can only be achieved through a paradigm shift from a security approach to an inclusive model of secularism based on human rights that accommodates pluralism without discrimination. The novelty lies in integrating postcolonial critique with Bourbeau’s securitization to explain gendered Islamophobia in French laïcité. Keywords : Laïcité, Structural Islamophobia, France.